Decoding the Genomic Variability among Members of the Bifidobacterium dentium Species - Lugli, Gabriele Andrea; Tarracchini, Chiara; Alessandri, Giulia; Milani, Christian; Mancabelli, Leonardo; Turroni, Francesca; Neuzil-Bunesova, Vera; Ruiz, Lorena; Margolles, Abelardo; Ventura, Marco (Microorganisms, 2020)
Members of the Bifidobacterium dentium species are usually identified in the oral cavity of humans and associated with the development of plaque and dental caries. Nevertheless, they have also been detected from fecal samples, highlighting a widespread distribution among mammals. To explore the genetic variability of this species, we isolated and sequenced the genomes of 18 different B. dentium strains collected from fecal samples of several primate species and an Ursus arctos. Thus, we investigated the genomic variability and metabolic abilities of the new B. dentium isolates together with 20 public genome sequences. Comparative genomic analyses provided insights into the vast metabolic repertoire of the species, highlighting 19 glycosyl hydrolases families shared between each analyzed strain. Phylogenetic analysis of the B. dentium taxon, involving 1140 conserved genes, revealed a very close phylogenetic relatedness among members of this species. Furthermore, low genomic variability between strains was also confirmed by an average nucleotide identity analysis showing values higher than 98.2%. Investigating the genetic features of each strain, few putative functional mobile elements were identified. Besides, a consistent occurrence of defense mechanisms such as CRISPR-Cas and restriction-modification systems may be responsible for the high genome synteny identified among members of this taxon.
Keywords: pangenome; genomics; phylogeny; bifidobacteria